2017
DOI: 10.2903/j.efsa.2017.4713
|View full text |Cite
|
Sign up to set email alerts
|

Safety of vitamin D3 addition to feedingstuffs for fish

Abstract: During 2012-2014, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) issued three opinions on the safety and efficacy of vitamin D 3 for all animal species and concluded that no safety concern was identified for the use of vitamin D 3 for fish at the maximum authorised content of 0.075 mg/kg feed. The Norwegian Food Safety Authority made available to the Commission some studies on the safety of vitamin D 3 for fish and consumers at substantially higher levels (1.5 mg/kg feed) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The nutritional profile of fish modified by the new scenarios might deserve more attention in the RBA; for instance, the use of vegetable oils can significantly modulate the lipid profile in fish flesh, depending on the oil and fish species ( 71 ), e.g., resulting in a decrease of omega 3 fatty acids ( 73 , 74 ). The novel, vegetable-based, aquaculture feeds were reported to cause a lowering of the fat-soluble vitamin D3 in fish, supporting a request to EFSA to assess the safety of higher addition levels of this vitamin, with the goal of improving both animal and human nutrition ( 75 ). The assessment represented an interesting example of RBA with “neutral” outcome: it recognized that the increasing use of plant-based feed materials in aquaculture feeds could induce a decrease in vitamin D3 content in feedingstuffs; however, there was no evidence that the current total (background + supplemented) maximum EU content of vitamin D3 could cause any appreciable risk of deficiency in salmonids, as the best investigated fish group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The nutritional profile of fish modified by the new scenarios might deserve more attention in the RBA; for instance, the use of vegetable oils can significantly modulate the lipid profile in fish flesh, depending on the oil and fish species ( 71 ), e.g., resulting in a decrease of omega 3 fatty acids ( 73 , 74 ). The novel, vegetable-based, aquaculture feeds were reported to cause a lowering of the fat-soluble vitamin D3 in fish, supporting a request to EFSA to assess the safety of higher addition levels of this vitamin, with the goal of improving both animal and human nutrition ( 75 ). The assessment represented an interesting example of RBA with “neutral” outcome: it recognized that the increasing use of plant-based feed materials in aquaculture feeds could induce a decrease in vitamin D3 content in feedingstuffs; however, there was no evidence that the current total (background + supplemented) maximum EU content of vitamin D3 could cause any appreciable risk of deficiency in salmonids, as the best investigated fish group.…”
Section: Discussionmentioning
confidence: 94%
“…The assessment represented an interesting example of RBA with “neutral” outcome: it recognized that the increasing use of plant-based feed materials in aquaculture feeds could induce a decrease in vitamin D3 content in feedingstuffs; however, there was no evidence that the current total (background + supplemented) maximum EU content of vitamin D3 could cause any appreciable risk of deficiency in salmonids, as the best investigated fish group. Also in regard of human nutrition and safety, notwithstanding many uncertainties, there was no evidence that increasing the level of vitamin D3 in feedingstuffs may lead to an important increase of the vitamin in fish flesh; therefore, the increased supplementation will lead neither to exceeding the UL, even in high consumers, nor to a significant contribution to reduce the human deficiency ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…New drugs have been tested in zebrafish for decades [ 65 , 66 ]. Specifically for this work, the cholecalciferol pathway is conserved in adult zebrafish [ 67 ]; similar to other vertebrates, VitD is metabolized to 25-hydroxycholecalciferol and then to 1,25-dihydroxycholecalciferol in zebrafish liver [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…When Atlantic salmon was fed 80,000 IU/kg (2 mg/kg) dietary VD 3 , the transfer ratio was 0.1–0.13 124,125 ; however, when Atlantic salmon were fed 8000 IU/kg (0.2 mg/kg) dietary VD 3 , the transfer ratio increased to 0.4 125 . In the unpublished data from the Denmark and Portugal governments, the transfer rate of 56,000 IU/kg (1.4 mg/kg) dietary VD 3 in salmon is 0.07, and 30,000 IU/kg (0.75 mg/kg) dietary VD 3 in rainbow trout is 0.16 121 . Data show that the upper limit of VD intake per day for adults and children is 100 and 50 μg, respectively 126 .…”
Section: Physiological Function Of Vd3 In Fishmentioning
confidence: 93%
“…On the other hand, fish appear to be very tolerant to high concentrations of VD 3 in their diet; most studies have not reported negative outcomes associated with high dietary concentrations of VD 3 . The Norwegian Food Safety Authority even proposed that fish, especially salmonids, have a safe upper limit of 60,000 IU/kg of dietary VD 3 121 …”
Section: Physiological Function Of Vd3 In Fishmentioning
confidence: 99%